Community Based Procurement : Value for Money Analysis - World Bank (World Bank, Washington, DC, 2013)
In the India operations of the World Bank, there is little evidence as yet to substantiate that community based procurement results in value for money in a fair and transparent manner. In order to understand community based procurement in relation to Value for Money (VFM), governance and accountability, a study was needed to explore these concepts and their dynamics. The present study focuses on Community Based Procurement (CBP) outcomes across completed sub-projects. The study on CBP was carried out in 84 successful subprojects from three Community Driven Development (CDD) projects in India (in the states of Andhra Pradesh, Madhya Pradesh and Tamil Nadu) and local government units (Gram Panchayats) in the state of Kerala, to explore linkages both in terms of enablers and outcomes. The study considers only completed and successful sub-projects to determine reasons that led to its success. The findings may have been impacted positively by this purposive selection.